A facile, solvent vapor–fumigation-induced, self-repair recrystallization of CH3NH3PbI3 films for high-performance perovskite solar cells1. Issue 12 (28th March 2015) - Zhu, Weidong; Yu, Tao; Li, Faming; Bao, Chunxiong; Gao, Hao; Yi, Yong; Yang, Jie; Fu, Gao; Zhou, Xiaoxin; Zou, Zhigang
<x xml:space="preserve">Abstract</x> Self-repair of poor CH3NH3PbI3 films to uniform ones by DMF vapor fumigation, enhancing cell efficiency from 5.07% to 11.15%.